Оцінка наявності ендотеліальної дисфункції у дітей з пурпурою Шенлейн-Геноха за показниками ультразвукової доплерографії = Evaluation of the presence of endothelial dysfunction in children with Henoch-Schonlein purpura in terms of doppler ultrasound - Veronika M. Dudnyk; Tatyana G. Korol (Kazimierz Wielki University, 2015)
Dudnyk V M, Korol T G. Оцінка наявності ендотеліальної дисфункції у дітей з пурпурою Шенлейн-Геноха за показниками ультразвукової доплерографії = Evaluation of the presence of endothelial dysfunction in children with Henoch-Schonlein purpura in terms of doppler ultrasound. Journal of Education, Health and Sport. 2015;5(2):33-44. ISSN 2391-8306. DOI: 10.5281/zenodo.14922 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A33-44 https://pbn.nauka.gov.pl/works/534637 http://dx.doi.org/10.5281/zenodo.14922 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.01.2015.     УДКУДК: 616 - 005.151 - 053:611.018.74: 616 - 008.6:615.03 ОЦІНКА НАЯВНОСТІ ЕНДОТЕЛІАЛЬНОЇ ДИСФУНКЦІЇ У ДІТЕЙ З ПУРПУРОЮ ШЕНЛЕЙН-ГЕНОХА ЗА ПОКАЗНИКАМИ УЛЬТРАЗВУКОВОЇ ДОПЛЕРОГРАФІЇ   Evaluation of the presence of endothelial dysfunction in children with Henoch-Schonlein purpura in terms of Doppler ultrasound   В.М.Дудник, Т.Г.Король VM Dudnyk, TG Korol   Вінницький національний медичний університет ім. М.І. Пирогова, кафедра педіатрії № 2 Vinnitsa National Medical University, Pediatrics department №2   Резюме Мета роботи - оцінити наявність ендотеліальної дисфункції при пурпурі Шенлейн - Геноха у дітей за показниками ультразвукової доплерографії. Матеріал і методи. Нами обстежено 123 дитини з  пурпурою  Шенлейн - Геноха віком від 1 до 18 років. Оцінку функціонального стану і вазорегуляторної функції судинного ендотелію проводили за допомогою ультразвукової доплерографії на УЗ-сканері "Philips HDII XE" в В-режимі датчиком лінійного формату в частотному діапазоні від 5 до 15 МГц в стані спокою. Результати. За показниками ультразвукової доплерографії, нами встановлено, що ендотеліальна дисфункція спостерігається у всіх дітей, хворих на пурпуру Шенлейн - Геноха. У пацієнтів з максимальною активністю захворювання показники структурного і функціонального стану ендотелію сонної і плечової артерій були в 1,3 - 1,5 рази більшими аналогічних показників практично здорових дітей. Також більш виражені порушення гемодинамічних характеристик кровотоку по плечовій артерії (зменшення швидкості) спостерігались при III ступені активності і складали - Vsp 34,59 ± 3,18 мм / сек, Ved 2,72 ± 0,57 мм / сек, S / D 10,15 ± 0,82.   Ключові слова: пурпура Шенлейн - Геноха, діти, ендотеліальна дисфункція, ультразвукова доплерографія.   Abstract Purpose - to assess the presence of endothelial dysfunction in children with Henoch-Schonlein purpura in terms of Doppler ultrasound. Material and methods. We examined 123 children with Henoch - Schonlein purpura from 1 to 18 years old. Assessment of functional status and vasoregulatory vascular endothelial function was performed using Doppler ultrasound using ultrasound scanner "Philips HDII XE" B-mode sensor linear format in the frequency range from 5 MHz to 15 MHz at rest. The Results. Using doppler ultrasound, we found that the endothelial dysfunction observed in all children with at Henoch - Schonlein purpura. In patients with maximum disease activity index of structural and functional state of the endothelium of the carotid and brachial arteries were 1.3 - 1.5 times more than in healthy children. Also, more severe violations of hemodynamic characteristics of blood flow in the brachial artery (speed reduction) were observed at the III degree of activity and accounted for - Vsp 34,59 ± 3,18 mm / sec, Ved 2,72 ± 0,57 mm / sec, S / D 10 15 ± 0,82.   Keywords: Henoch - Schonlein purpura, children, endothelial dysfunction, Doppler ultrasound.